2012
DOI: 10.1371/journal.pone.0051795
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs in Relative Limb Length among Peruvian Children: Extending the Thrifty Phenotype Hypothesis to Limb Proportions

Abstract: Background and MethodsBoth the concept of ‘brain-sparing’ growth and associations between relative lower limb length, childhood environment and adult disease risk are well established. Furthermore, tibia length is suggested to be particularly plastic under conditions of environmental stress. The mechanisms responsible are uncertain, but three hypotheses may be relevant. The ‘thrifty phenotype’ assumes that some components of growth are selectively sacrificed to preserve more critical outcomes, like the brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 79 publications
9
123
1
1
Order By: Relevance
“…The tibia is more susceptible to periods of poorer health than the femur (Bogin and Varela-Silva 2008), thus also reduced oxygen supply is likely to impact bone growth at a critical time during development (Bailey and Hu 2001). Reduced tibia length was also observed among Tibetan and Peruvian children at HA (Stinson and Frisancho 1978;Bailey and Hu 2001;Pomeroy et al 2012), the latter also showing reduction of forearm length. This suggests hypoxia's effect on distal limb segments, though other climatic factors cannot be excluded.…”
Section: Discussionmentioning
confidence: 82%
“…The tibia is more susceptible to periods of poorer health than the femur (Bogin and Varela-Silva 2008), thus also reduced oxygen supply is likely to impact bone growth at a critical time during development (Bailey and Hu 2001). Reduced tibia length was also observed among Tibetan and Peruvian children at HA (Stinson and Frisancho 1978;Bailey and Hu 2001;Pomeroy et al 2012), the latter also showing reduction of forearm length. This suggests hypoxia's effect on distal limb segments, though other climatic factors cannot be excluded.…”
Section: Discussionmentioning
confidence: 82%
“…However, the results also identify phenotypic variation among the negritos, particularly in the form of narrower pelves among the Andaman Islanders compared with the Aeta, but also higher brachial indices. Differences in the Andaman Islander and Aeta lower limbs were reflected in the length of the femur, the proximal limb segment, rather than the more "plastic" distal limb segment (tibia), which appears to be more sensitive to environmental stress (Pomeroy et al 2012). In general, the characteristics of narrow bi-iliac breadths and short crural indices are shared with Southern African hunter-gatherers and not other Asian populations.…”
Section: Discussionmentioning
confidence: 90%
“…In this case, an initial shift towards smaller body size could correspond with climatic warming associated with the onset of the Holocene. Recent research has suggested that limb segment lengths may be influenced by 'thrifty' phenotypic mechanisms and exposure to environmental stress [64]. In this context, a decrease in body size associated with the transition to agriculture could be a plastic response to dietary stress.…”
Section: Discussionmentioning
confidence: 99%